2007
DOI: 10.1523/jneurosci.1320-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Receptive Fields of Midbrain Neurons Elicited by Thalamic Electrical Stimulation through Corticofugal Feedback

Abstract: The ascending and descending projections of the central auditory system form multiple tonotopic loops. This study specifically examines the tonotopic pathway from the auditory thalamus to the auditory cortex and then to the auditory midbrain in mice. We observed the changes of receptive fields in the central nucleus of the inferior colliculus of the midbrain evoked by focal electrical stimulation of the ventral division of the medial geniculate body of the thalamus. The receptive field of an auditory neuron wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 62 publications
(76 reference statements)
2
34
0
Order By: Relevance
“…Indeed, studies using iontophoresis to block inhibition within the IC have shown that the removal of either GABAergic or glycinergic inhibition can change the spectral (Vater et al, 1992;Yang et al, 1992;Palombi and Caspary, 1996;LeBeau et al, 2001) and temporal response properties of individual neurons (Koch and Grothe, 1998;Caspary et al, 2002), and can also result in the weakening of inhibitory regions in the STRF (Andoni et al, 2007). A previous study has shown that similar changes in the response properties of IC neurons can also be observed after manipulation of activity in the thalamus and cortex, suggesting that some of the intensity-dependent changes in STRFs that we observe in the IC may also reflect changes in other brain regions (Wu and Yan, 2007).…”
Section: Relation To Previous Studies Of Intensity-dependent Nonlineasupporting
confidence: 66%
“…Indeed, studies using iontophoresis to block inhibition within the IC have shown that the removal of either GABAergic or glycinergic inhibition can change the spectral (Vater et al, 1992;Yang et al, 1992;Palombi and Caspary, 1996;LeBeau et al, 2001) and temporal response properties of individual neurons (Koch and Grothe, 1998;Caspary et al, 2002), and can also result in the weakening of inhibitory regions in the STRF (Andoni et al, 2007). A previous study has shown that similar changes in the response properties of IC neurons can also be observed after manipulation of activity in the thalamus and cortex, suggesting that some of the intensity-dependent changes in STRFs that we observe in the IC may also reflect changes in other brain regions (Wu and Yan, 2007).…”
Section: Relation To Previous Studies Of Intensity-dependent Nonlineasupporting
confidence: 66%
“…Thus, for this class, the excitatory IC inputs to MGB neurons are inhibited by convergent inputs from neighboring channels, perhaps enabling a sharpening of the receptive field (27). Bartlett and Smith (11,12) found a similar class of mixed inputs, which were further segregated based on the temporal sequence of excitation and inhibition.…”
Section: Discussionmentioning
confidence: 95%
“…Forty-one female C57 mice (Charles River Laboratories) aged 4 -7 weeks and weighing 14.6 -24.0 g were used in this study. Animal preparation, acoustic stimulation, electrical stimulation of the auditory cortex, recording of action potentials and data processing were mostly the same as those described previously (Yan and Ehret, 2002;Jafari et al, 2007;Wu and Yan, 2007). All protocols and procedures were in accordance with the Canadian Council on Animal Care and approved by the Animal Care Committee of the University of Calgary (protocol number: M04044).…”
Section: Methodsmentioning
confidence: 99%